Effective carbon nanotubes/graphene hybrid films for electron field emission application. (November 2019) - Hong, Xuda; Shi, Wei; Zheng, Hairong; Liang, Dong
Abstract: In this study, carbon nanotubes (CNTs) are combined with graphene to form effective CNTs/graphene hybrid films for electron field emission by simple and facile electrophoretic deposition approach. The hybrid films exhibit lower turn-on and threshold field as well as larger field enhancement factor compared to those of pure CNTs and pure graphene films. A pulse high voltage is applied to achieve a high emission current from the hybrid films. A fairly high emission current of 80 mA (160 mA/cm 2 ) is obtained, which is greatly larger than the maximum current achieved under continuous high voltage. The pulsewidth affects the field emission properties of the hybrid films due to the current heating effect and should be strictly limited. The hybrid films also show good long-term stability under pulse high voltage. Furthermore, a Preliminary study is presented using the CNTs/graphene hybrid films as cold cathode of a X-ray source. These results demonstrate that CNTs/graphene hybrid films can be a potential candidate for vacuum electron source. Highlights: The CNTs arecombined with graphene to formeffective hybrid films. . The CNTs/graphene hybrid films show goodfield emissionproperties. . AX-ray sourceusing the hybrid filmsas electron emission source is presented.